Strategi Komunikasi Bisnis Yang Efektif Dalam Membangun Hubungan Dengan Klien - Lola Astrid Gultom; Fretty Hizkia Sinaga; Gracsela Zalukhu; Ica Maeisa; Johan Untung Sidebang; Suryani Sihombing; Lampola Sitorus P; Dio Aprinus Parluhutan Hutasoit (LPPM Universitas HKBP Nommensen, 2025)
Effective business communication determines a company's success amid fierce competition and technological advances. This communication builds lasting relationships and client trust, enhancing image and loyalty. Address cultural challenges and interpersonal skills in the digital age through an open culture, communication training, and feedback. The keys to success: analyzing client behavior, maintaining consistent transparency, and balancing digital and personal communication to build emotional connections and competitive advantage.